The Effect of Problem-Based Learning (PBL) with Diorama Media on Understanding Science Concepts - Johar Mahliga Putri; Syahriani Yulianci; Rizalul Fiqry (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
This study aims to test the Problem-Based Learning (PBL) model, supported by diorama media, in improving students’ understanding of science concepts related to food chains. The study employed a quasi-experimental method with a One-Group Pretest–Posttest design. The study subjects consisted of 15 fifth-grade students from SDN Penapali, selected through saturation sampling. Data were collected via tests, observations, and documentation, then analyzed using the Shapiro–Wilk normality test and a paired-sample t-test with the assistance of Jamovi software. The analysis results indicated that the data were normally distributed (p > 0.05). Hypothesis testing revealed a significant difference between pretest and posttest scores (p < 0.001) with an effect size classified as very large. These findings confirm that  implementing of the Problem-Based Learning (PBL) model aided by diorama media significantly and effectively improves students’ understanding of science concepts. The integration of problem-based learning with concrete media has proven capable of strengthening student engagement and facilitating deeper knowledge construction. Therefore, this approach is recommended as an innovative strategy in science education at the elementary school level.